Ritual Analysis of Baduy Tribe in Maintaining Culture - Fitriyani, Fitriyani; Nisa, Nita Haerun; Yudhiyanto, Teguh; Khoiriyah, Eneng Liah; Khairunnisa, Iim (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2023)
Sundanese culture is an example of diversity in Indonesia. This culture developed in West Java with positive values applied by each community. The importance of preserving and passing on these teachings to the younger generation does not only apply to the Sundanese community, but also relates to the observance of the Baduy tribe from Banten. This tribe maintains its traditions and special bonds strongly. This research uses an ethnographic approach with qualitative analysis, involving interviews and observations. The obedience of the Baduy community is a concrete example of moral values that encourage us to follow certain principles. Obeying customs and regulations does not mean being stagnant; on the contrary, there are many moral values that we can take from the Baduy community as an example.